Twilight people : one man's journey to find his roots - Houze, David, 1965- (Berkeley : University of California Press, 2006)
Triggers a journey of self-discovery and reconnection that ranges from the shores of South Africa to the dirty roads of Mississippi - and back. This narrative uses the unraveling mystery of Houze's family and his quest for identity as a prism through which to view the tumultuous events of the civil rights movement in Mississippi.
Author's Note; Prologue; 1. From Down South to Down South; 2. Into the Breach; 3. Truth and Reconciliation; Epilogue; Postscript; Acknowledgments; Notes; Bibliography; Index.
"The George Gund Foundation imprint in African American studies."
Includes bibliographical references (pages 291-320) and index.
Print version record and CIP data provided by publisher; resource not viewed.
English.
JSTOR
Keywords: Houze, David, -- 1965-; Houze, David, -- 1965-; African Americans -- Biography; African Americans -- Civil rights -- Southern States -- History -- 20th century; Civil rights movements -- Southern States -- History -- 20th century; Southern States -- Race relations; Apartheid -- South Africa; South Africa -- Race relations; Siblings; Sibling Relations; Noirs américains -- Biographies; Noirs américains -- Droits -- États-Unis (Sud) -- Histoire -- 20e siècle.; Mouvements des droits de l'homme -- États-Unis (Sud) -- Histoire -- 20e siècle.; États-Unis (Sud) -- Relations raciales; Apartheid -- Afrique du Sud; Afrique du Sud -- Relations raciales; Frères et sœurs; siblings (people); TRAVEL; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY -- Social History; African Americans; African Americans -- Civil rights; Apartheid; Siblings; Civil rights movements; Race relations; South Africa; Southern States; 1900-1999; Autobiography; Biography; autobiographies (literary works); Autobiographies; Biographies; History; Autobiographies; Biographies; Autobiographies; Biographies